The economic impact of health care provision: a CGE assessment for the UK - Rutten, Martine (2004)
This thesis seeks to determine the macro-economic impacts of changes in health care provision, whilst recognising the simultaneous effects of consequent changes in health on effective labour supplies and the resource claims made by the health care sector. The resource allocation issues have been explored in theory, by developing an extension of the standard Rybczynski theorem from a low-dimension Heckscher-Ohlin framework, and empirically, by developing a Computable General Equilibrium model, calibrated to a purpose-built dataset for the UK.